Indigenous Semiotics in “The Transistor” by Shahnaz Bashir: Application of Roland Barthes’ Codes to Kashmiri Narrative - Abbas, Mazhar; Nadeem, Farrukh; Kharal, Ali Ahmad (Pakistan Journal of Humanities and Social Sciences, 2021)
The research focuses on the indigenous critical perspective when applied through semiotics of Barthes’ codes to the Kashmiri narratives. The study briefly reviews indigenous perspective as explained by Professor Jody Byrd and Aileen Moreton-Robinson after giving reference to Heather Harris about indigenous epistemology. This follows linking it to semiotics through Barthes’ codes with their review and association to cultural indigenousness. The research also reviews the Kashmiri narrative tradition and analyses the short story “The Transistor” in the light of this theoretical perspective to show that Kashmiri indigenousness as presented through signs and symbols when interpreted as indigenous semiotics show the specific Kashmiri resistance, conflictual cultural practices, and indigenous sovereignty under paracolonialism. The research, however, falls short of proving how the Kashmiri cultural paradigm shifts under paracolonial presence which requires separate inquiry from another angle.